Effects of Anion Impurities on the Solubility and Nucleation of Borax Decahydrate Crystals in Carbonate-Type Brine - Jing Chen; Jiaoyu Peng; Xingpeng Wang; Yaping Dong; Wu Li (Crystals, 2019)
Measurements of the solubility and metastable zone width (MSZW) of borax decahydrate (disodium tetraborate decahydrate) within chloride, sulfate and carbonate solutions were carried out. The MSZW was measured by the conventional polythermal method with turbidity technology. The results showed that the addition of impurities decreased solubility. The main factor reducing solubility is the common ion effect, but the salt effect is also significant in the complex system. The addition of impurities broadened the MSZW. The MSZW was wider at first, then decreased with the addition of NaCl, yet the MSZW widened with the addition of Na2SO4 within the concentration range studied. This can be explained by adsorption and diffusion. The data of solubility and MSZW were analyzed by applying the Van’t Hoff equation and the classical 3D nucleation theory approach, respectively. By calculating the corresponding parameters, the experimental phenomena are further explained from the perspective of thermodynamics and dynamics.